2022
DOI: 10.2460/javma.22.03.0125
|View full text |Cite
|
Sign up to set email alerts
|

Fewer peripheral intravenous catheter complications in hospitalized dogs when force-activated separation devices are used versus not used in a randomized controlled clinical trial

Abstract: OBJECTIVE To determine whether the use of a force-activated separation device (FASD) lowers the incidence risk of peripheral intravenous catheter (PIVC) complications in hospitalized dogs. ANIMALS 367 dogs that were hospitalized and received IV fluids between January 11 and March 25, 2021. PROCEDURES A prospective, randomized controlled clinical trial was performed. Dogs hospitalized and receiving IV fluids for at least 24 hours were randomized to the FASD group or control group. PIVCs were placed followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[21][22][23] Identifying the specific factors associated with dislodgement was beyond the scope of our study; however, twice-daily assessments may have led to loosening of the dressing, and patient mobility or positioning might have contributed to our overall dislodgement rate. Force-activated separation devices, although not used in our study, have shown promise in reducing PIVC complications in dogs, 9 suggesting potential for future investigation in cats. Overall, our study suggested that maintaining clean, dry, and intact PIVC dressings, along with secure catheter placement, may aid in reducing dislodgement rates.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…[21][22][23] Identifying the specific factors associated with dislodgement was beyond the scope of our study; however, twice-daily assessments may have led to loosening of the dressing, and patient mobility or positioning might have contributed to our overall dislodgement rate. Force-activated separation devices, although not used in our study, have shown promise in reducing PIVC complications in dogs, 9 suggesting potential for future investigation in cats. Overall, our study suggested that maintaining clean, dry, and intact PIVC dressings, along with secure catheter placement, may aid in reducing dislodgement rates.…”
Section: Discussionmentioning
confidence: 86%
“…In veterinary medicine, PIVC-related complications have been described as extravasation, phlebitis, dislodgment, occlusion, line breakage, and patient removal. [3][4][5][6][7][8][9] Noninfectious PIVC complication rates…”
mentioning
confidence: 99%
See 1 more Smart Citation